Lifting the lid, 2 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
'I am an extension officer as well as a practicing farmer, writes Ama Ukoha from Aba, Aria State, Nigeria. Often, contributors to Spore have proffered solutions to my immediate problems, such as the drip irrigation technique featured in Spore of...